Adjoining a Constant Function to n-Dimensional Chebyshev Space - Mansour Alyazidi-Asiry (Journal of Function Spaces)
This paper is concerned with extending a Chebyshev system of n continuous nonconstant functions into a set of n+1 functions including a constant function. Necessary and sufficient conditions for the new set to be a Chebyshev system are discussed and some results are obtained.